Analisis Peningkatan Produktivitas UKM Pada Usaha Alat Kebrsihan Rumah Tangga Melalui enjualan E-commerce Pada Toko Ucimop di Desa Karang Tengah Kecamatan Purwosari Kabupaten Pasuruan - Muhammad Sonhaji; Muhammad Fahmul Iltiham; Muhammad Nizar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this era of globalization, SMEs (Small and Medium Enterprises) play a vital role in driving a country's economy. In this context, increasing the productivity of SMEs is an urgent matter to be considered, given the increasingly fierce competition and dynamic changes in market trends. Sales through e-commerce platforms have become an increasingly dominating trend in the world of commerce. With an increasingly digitally connected market, the existence of an online store has become a necessity for SMEs to remain competitive. Ucimop SME in Karang Tengah Village, Purwosari District, Pasuruan Regency, is one example of an SME engaged in the business of household cleaning tools and has utilized an e-commerce platform to expand their market reach. This type of research is qualitative research. The result of this research is that the presence of E-commerce is one of the marketing alternatives used to reach more customers. MSMEs can conduct promotions anywhere and anytime for 24 hours without stopping. This transaction model allows transactions to cross regional boundaries much more easily and cost effectively than traditional trade.